Espécies de plantas do banco de germoplasma forrageiro da FCAV/UNESP Jaboticabal - Versuti, Jonathan [UNESP]; Assumpção, Fabiana Marques de [UNESP]; Vazquez, Velizie Caldarelli [UNESP]; Tosi, Lucas Ariel [UNESP]; Carneiro, André Portella [UNESP]; Raposo, Elisamara [UNESP]; Nascimento, Tiago Silva do; Spasiani, Paola Palauro [UNESP]; Ruggieri, Ana Cláudia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The choice of forage species is extremely important to animal production systems implementation. Germplasm collection from the Forage and Pastures sector at Agriculture and Veterinary Sciences College, UNESP, Jaboticabal, this germplasm collection aims to preserve and disclose the plant species used in animal feeding or green fertilization. Germplasm collection is currently composed of 99 sites covering an area of approximately 0.6 hectares. Germplasm collection includes 69 grass species, 29 legumes species and only one species of cactaceae family. Germplasm collection is used for teaching, research, exchange of materials and disclosure for farmer and others educational meanings.

A escolha da espécie forrageira é de extrema importância na implantação de um sistema de produção animal a pasto. O banco de germoplasma do Setor de Forragicultura e Pastagens da Faculdade de Ciências Agrárias e Veterinárias, UNESP, Câmpus de Jaboticabal, tem como objetivo preservar e difundir as espécies de plantas que podem ser utilizadas na alimentação animal ou em adubação verde. O banco atualmente é composto por 99 canteiros que ocupam uma área de aproximadamente 0,6 hectares. A coleção conta com 69 espécies de gramíneas, 29 espécies de leguminosas e uma espécie da família cactaceae. O banco é utilizado para aulas práticas, pesquisas, intercâmbio com outras instituições e divulgação do banco para produtores.
Keywords: Grass; Legumes; Grazing; Gramínea; Leguminosa; Pastagem